2009
DOI: 10.5194/acpd-9-22833-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Model of optical response of marine aerosols to Forbush decreases

Abstract: Abstract. In order to elucidate the effect of galactic cosmic rays on cloud formation, we investigate the optical response of marine aerosols to Forbush decreases – abrupt decreases in galactic cosmic rays – by means of modeling. We vary the nucleation rate of new aerosols, in a sectional coagulation and condensation model, according to changes in ionization by the Forbush decrease. From the resulting size distribution we then calculate the aerosol optical thickness and Angstrom exponent, for the wavelength pa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Based on surface aerosol measurements at one site, Kulmala et al (2010) found no connection between the cosmic ray flux and new particle formation or any other aerosol property over a solar cycle (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008), although particles nucleated in the free troposphere are known to contribute to particle number and CCN concentrations in the boundary layer (Merikanto et al, 2009). Our understanding of the 'ion-aerosol clear air' mechanism as a whole relies on a few model investigations that simulate changes in cosmic ray flux over a solar cycle (Pierce and Adams, 2009b;Snow-Kropla et al, 2011;Kazil et al, 2012) or during strong Forbush decreases (Bondo et al, 2010;Snow-Kropla et al, 2011;Dunne et al, 2012). Changes in CCN concentrations due to variations in the cosmic ray flux appear too weak to cause a significant radiative effect because the aerosol system is insensitive to a small change in the nucleation rate in the presence of pre-existing aerosols (see also Section 7.3.2.2).…”
Section: Physical Mechanisms Linking Cosmic Rays To Cloudinessmentioning
confidence: 99%
“…Based on surface aerosol measurements at one site, Kulmala et al (2010) found no connection between the cosmic ray flux and new particle formation or any other aerosol property over a solar cycle (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008), although particles nucleated in the free troposphere are known to contribute to particle number and CCN concentrations in the boundary layer (Merikanto et al, 2009). Our understanding of the 'ion-aerosol clear air' mechanism as a whole relies on a few model investigations that simulate changes in cosmic ray flux over a solar cycle (Pierce and Adams, 2009b;Snow-Kropla et al, 2011;Kazil et al, 2012) or during strong Forbush decreases (Bondo et al, 2010;Snow-Kropla et al, 2011;Dunne et al, 2012). Changes in CCN concentrations due to variations in the cosmic ray flux appear too weak to cause a significant radiative effect because the aerosol system is insensitive to a small change in the nucleation rate in the presence of pre-existing aerosols (see also Section 7.3.2.2).…”
Section: Physical Mechanisms Linking Cosmic Rays To Cloudinessmentioning
confidence: 99%
“…The Chree method (Chree, 1912(Chree, , 1913 of Superposed Epoch Analysis (SEA) dominates literature documenting the relationships of Fds with geomagnetic disturbance indexes (Kane, 2010), IMF parameters (Pankaj and Shukla, 1994), magnetic clouds (Badruddin et al, 1991;Ananth and Venkatesan, 1993), terrestrial clouds (Pudovkin and Veretenenko, 1995;Svensmark et al, 2009), marine aerosols (Bondo et al, 2010), atmospheric electricity (Marcz, 1997), solar flares (Belov et al, 2008) and CMEs (Pankaj and Singh, 2005). Some researchers (see, for example, Pankaj and Shukla (1994) and Kane (2010)) base the use of SEA on the assumption of global simultaneity of Fds at one or more stations.…”
Section: Introductionmentioning
confidence: 99%
“…However, from a modeling point of view, it is uncertain whether a variation in ion‐induced nucleation may translate into an observable change in cloud condensation nuclei (CCN) and thus in clouds. Bondo et al [] suggest that an aerosol effect could be observable under atmospheric conditions while general circulation modeling gives rise to much smaller responses in the CCNs [ Kazil et al , ; Pierce and Adams , ; Snow‐Kropla et al , ; Yu and Luo , ]. Of these studies, Yu and Luo [] find a response almost an order of magnitude larger than previous estimates but still insufficient to explain the large observed variations in the ocean heat content over the solar cycle [ Shaviv , ; Howard et al , ].…”
Section: Introductionmentioning
confidence: 99%